2016
DOI: 10.1123/jab.2015-0246
|View full text |Cite
|
Sign up to set email alerts
|

Postural Balance Parameters as Objective Surgical Assessments in Low Back Disorders: A Systematic Review

Abstract: Balance assessments could render useful objective performance measures to evaluate the efficacy of low back surgeries, yet these assessments have not been collectively examined to determine longitudinal sensitivity across surgical interventions. The purpose of this review was to determine sensitivity of balance measurements for disparate spinal disorders after surgical intervention. We searched PubMed, Embase, Scopus, the Cochrane Library, Web of Science, and CINAHL. Articles were selected based on: (1) sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The examination of quiet-stance postural control by assessing body sway characteristics during quiet standing is routinely used in research and practice in several fields related to human health and human movement ( Piirtola and Era, 2006 ; Ku et al, 2014 ; Yen et al, 2016 ; Roman-Liu, 2018 ; Kozinc et al, 2020 ). For instance, variables related to center of pressure (CoP) movement may be used to determine the risk of falling in older adults ( Piirtola and Era, 2006 ; Kozinc et al, 2020 ) and to assess balance deficits in Parkinson’s disease patients ( Gera et al, 2016 ; Feller et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of quiet-stance postural control by assessing body sway characteristics during quiet standing is routinely used in research and practice in several fields related to human health and human movement ( Piirtola and Era, 2006 ; Ku et al, 2014 ; Yen et al, 2016 ; Roman-Liu, 2018 ; Kozinc et al, 2020 ). For instance, variables related to center of pressure (CoP) movement may be used to determine the risk of falling in older adults ( Piirtola and Era, 2006 ; Kozinc et al, 2020 ) and to assess balance deficits in Parkinson’s disease patients ( Gera et al, 2016 ; Feller et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…LBP manifests in altered movement patterns when walking or changing positions, and may interfere with both activities of daily living and work-related functions [ 31 , 32 ]. Along with in-clinic measures of function that have been extensively studied for LBP treatments [ 33 , 34 ], measures of daily activities can be utilized to objectively evaluate disability due to pain. We previously showed that fluoroscopy guided PSI for LBP improved in-clinic motor performance, which could last between one to three months [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…LBP manifests in altered movement patterns when walking or changing positions, and may interfere with both activities of daily living and work related functions [30,31]. Along with inclinic measures of function that have been extensively studied for LBP treatments [32,33], measures of daily activities can be utilized to objectively evaluate disability due to pain. We previously showed that fluoroscopy guided PSI for LBP improves in-clinic motor performance, which can last between one to three months [13].…”
Section: Differences Between Subjective and Objective In-clinic And Imentioning
confidence: 99%